On the relative order of adjectives in Old Irish - Ronan, Patricia (Studia Celtica Posnaniensia, 2024)
This study examines the relative order of adjectives in Early Irish and seeks to determine the preferred order of adjectives in the noun phrases in a corpus of Old and Middle Irish. To date, too little research exists on this topic in Early Irish: grammars of the language typically determine the outline of adjective use, and some recent research investigates factors determining pre- or post-modification (Linnemeier, 2024). Yet so far little is known about the distribution of adjectives in corpus data and which factors influence distribution. In particular, the question which role is played by date of composition or text category has not received enough attention. Thus, the current study uses a corpus-linguistic approach to determine the distribution of adjectives in a tagged corpus of Old and Middle Irish, the POMIC corpus (Lash 2014). To do so, the corpus search interface CorpusSearch 2 (Randall 2009) is used to detect complex noun phrases which involve one or more adjectives. The study provides some evidence for diachronic variation in the use of adjectives in Old and Middle Irish corpus data, but larger databases are needed to determine the relative influence of genre and time of composition. There are some indications, however, that previous mention of a concept and the use of parallel structures in other languages may influence prefixed or postnominal position of adjectives.